Cluster Analysis of Innovativeness in Manufacturing Companies and Its Influence to Business Success - Suroso, Edy; Primiana, Ina; Kaltum, Umi; Azis, Yudi (International Journal of Engineering and Technology, 2018)
The competition makes the companies under pressure to always survive in the conditions that dynamically changed. Innovation has been known as an important factor in improving the performance of the company in the face of dynamic market. The purpose of this paper are (1) to analyze innovativeness by using the 58 operations managers of manufacturing companies in Tasikmalaya City, West Java Indonesia as respondents, and (2) to know the types of innovativeness cluster determining business success. The results showed the four types of clusters of Innovativeness consisting (1) Leading Innovators cluster that have the outclass value than the others in every aspect of innovativeness, (2) Followers cluster is as the very low radical product innovations capability, (3) Inventors are very strong radical product innovations, while (4) Laggers are the lowest scores in all innovation types among the clusters. Based on ANOVA, it is concluded that every clusters of innovativeness has its own business success difference. The leading innovators type has the highest mean of business success measured by the comparison innovations type among clusters in the sales growth.Â Â